Primary Ciliary Signaling in the Skin—Contribution to Wound Healing and Scarring - Hosio, Mayu; Jaks, Viljar; Lagus, Heli; Vuola, Jyrki; Ogawa, Rei; Kankuri, Esko (Frontiers in Cell and Developmental Biology, 2020)
Primary cilia (PC) are solitary post-mitotic, microtubule-based and membrane-covered organelle protrusions that are found on almost every mammalian cell. They are specialized cellular sensory units that transmit environmental information to the cells. Signaling through the PC participates in the regulation of a variety of cellular processes including proliferation, differentiation, and migration. Defective or abnormal PC signaling contributes to pathological development, and their important role in development and function is further underscored by a family of genetic disorders, ciliopathies, related to mutations in genes affecting PC structure or function. In wound healing, for example, during the epithelial-myofibroblast transition (EMyT) and fibroblast-to-myofibroblast transition stimulated by transforming growth factor β (TGF-β), PC on a number of cell types involved undergo major alterations. Formation of pathological scars has been associated with abnormal fibroblast responses to extracellular cues, while the delay of fibroblast apoptosis has been linked with the production of excessive amounts of collagen resulting in the formation of keloids and hypertrophic scars. In this review, we focus on the PC in cells of the skin, the major signaling pathways associated with them, and their contribution to wound healing and scarring. We review the current understanding on PC signaling and the development of pathological scars as well as provide insight into the possible role of PC as targets for anti-scarring therapies.